WHY WAS ST GREGORY OF NYSSA NEVER CONDEMNED FOR HIS DOCTRINE OF APOKATASTASIS? - Ilaria L.E. RAMELLI (Studia Universitatis Babeș-Bolyai. Philosophia, 2022)
This article will first point out that St Gregory of Nyssa supported the doctrine of apokatastasis or universal restoration as grounded in Christ and in defence of Christian “orthodoxy” against Arian tendencies—as Origen, his great inspirer, had done against “Gnosticism”. In light of this, the reason why Gregory’s doctrine of apokatastasis was never condemned by the Church (differently from the case of Origen) will be asked, and several potential answers, which reinforce one another, will be offered. Finally, the essay will highlight the role of Gregory as a touchstone of orthodoxy.